The causal association of polyunsaturated fatty acids with allergic disease: A two-sample Mendelian randomization study - Li, Yajia; Li, Qiangxiang; Cao, Ziqin; Wu, Jianhuang (Frontiers in Nutrition, 2022)
Objectives: Previous studies have reported a potential association of polyunsaturated fatty acids (PUFAs) levels with allergic disease risk and the possible benefit of PUFAs supplementation on allergic disease prevention. This study was performed to estimate the genetic association between PUFAs and allergic diseases using the method of both univariable and multivariable two-sample Mendelian randomization (MR). Methods: As indicators of the PUFAs levels, we included the omega-3, omega-6, docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA), linoleic acid (LA), and the ratio of omega-6 to omega-3 (omega-6:3). Summarized statistics of genome-wide association studies (GWASs) for these PUFAs were obtained from the UK Biobank and the Twins UK cohort. Genetic data relating to allergic diseases, including atopic dermatitis (AD), allergic rhinitis (AR), allergic conjunctivitis (AC), allergic urticaria (AU) and asthma, were accessed from the FinnGen biobank analysis. Odds ratios and 95% CIs were used to express the impact. Results: The MR results denoted a genetic association between the genetically determined increase in omega-3 levels and the decreased risk of some allergic diseases including AD (OR: 0.863 ; 95% CI: 0.785 to 0.949; p=3.86E-03), AC (OR:0.720; 95% CI: 0.547 to 0.947; p=1.87E-02) and AU (OR:0.821; 95% CI: 0.684 to 0.985; p=3.42E-02), while omega-6 and DHA level was only found to have negatively correlation with risk of AC with ORs of 0.655 (95% CI: 0.445 to 0.964; p=3.18E-02) and 0.671 (95% CI 0.490 to 0.918; p=1.25E-02), respectively. Omega-6:3 were causally significantly associated with the increased risk of AD (OR:1.171; 95% CI: 1.045 to 1.312; p=6.46E-03) and AC (IVW: OR:1.341; 95% CI: 1.032 to 1.743; p=2.83E-02). After adjustment of age, economic level, BMI, smoking and alcohol behaviours in the multivariable MR analysis, a direct causal protective effect of omega-3 on AD and AC, as well as a direct causal association between DHA and AD were observed. Omega-6:3 was also found to be directly associated with an increased risk of AD and AC. No association was found of EPA or LA with allergic diseases. Conclusion: Higher PUFA concentrations (omega-3, omega-6, DHA) and lower omega-6:3 ratios were genetically associated with a lower risk of some allergic diseases.